Chapter 5.6 The Profession of Research Management and Administration in the Caribbean Community - Paul W. Ivey (Emerald Publishing Limited, 2023)
This chapter contextualises and provides an overview of the development and current state of the profession of research management and administration in the English-speaking Caribbean. In addition, the chapter shows that Research Management and Administration is an emerging profession that is beginning to take root in CARICOM countries, especially as demonstrated by the leading HEIs in which it is recognised that research administration functions are important in supporting and adding value to the research agendas of these institutions and their larger mission of contributing to the sustainable development of the region.
10.1108/978-1-80382-701-820231039; 10.1108/978-1-80382-701-820231039; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262